2020
DOI: 10.3892/ol.2020.12322
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes in lung adenocarcinoma based on a competing endogenous RNA network

Abstract: Lung adenocarcinoma (LUAD) is the most commonly diagnosed type of lung cancer and exhibits a high morbidity. The present study aimed to investigate the long non-coding RNA (lncRNA)-associated competing endogenous RNA (ceRNA) mechanisms in LUAD. The receptor activity modifying protein 2-antisense RNA 1 (RAMP2-AS1) was identified using GSE113852 and GSE130779 datasets downloaded from the Gene Expression Omnibus database, and the downregulation of RAMP2-AS1 was the most significant in LUAD. In addition, microRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, a long noncoding RNA was found to be encoded on the antisense strand of RAMP2 and was denoted RAMP2-AS1. RAMP2-AS1 regulates endothelial cell homeostasis and may also play a role in cancer-related angiogenesis ( Cheng et al, 2020 ; Hassani et al, 2021 ; Lai et al, 2021 ; Song et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a long noncoding RNA was found to be encoded on the antisense strand of RAMP2 and was denoted RAMP2-AS1. RAMP2-AS1 regulates endothelial cell homeostasis and may also play a role in cancer-related angiogenesis ( Cheng et al, 2020 ; Hassani et al, 2021 ; Lai et al, 2021 ; Song et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The AUCs of their established prognostic model for predicting patients' survival at 1, 3, and 5 years were 0.692, 0.722, and 0.651 in the test data, respectively. Song et al 16 reported fifty genes that may be associated with CD44, CCND3, NCALD, and MACF1 and suggested that miR-296-5p, RAMP2-AS1, CD44, CCND3, NCALD, and MACF1 may serve as potential reliable biomarkers for the detection of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…In LUAD, “high” expressing groups of both COL7A1 and NTSR1 demonstrated reduced NCALD, the gene whose low expression worsens patient outcome 89 . Furthermore, CCND3, whose high expression improves survival 79 , was reduced in the COL7A1 high group while CD44 , a promoter of KRAS-dependent lung tumorigenesis 90 , was elevated in the NTSR1 high group. Lastly, KRT1 high BLCA patients had significantly higher expression of EGFR and MKI67 , suggesting that proliferation is potentiated in this group; this complements the survival analysis (high KRT1 is unfavorable in BLCA) and IHC data ( KRT1 staining is higher in cancer than normal specimens).…”
Section: Discussionmentioning
confidence: 94%
“…All genes with satisfactory AUC were subjected to analysis of IHC data. Their influence on tumor progression was also evaluated; each cancer was considered separately, with progression-related genes being selected for BLCA 77 , ESCA 78 , LUAD 79 , PAAD 80 , 81 and UCEC 82 based on literature. The prognostic value of EMX2 suggests it as a favorable marker for DFS and the staining confirms that it is present at a higher level in normal endometrial tissue than in tumor, as noted previously 83 .…”
Section: Discussionmentioning
confidence: 99%